Host Suitability of Cover Crops to the Root-Lesion Nematode Pratylenchus penetrans Associated with Potato - Neupane, Kamal (Plant disease, 2023)
Nonhost or poor host cover crops can provide an alternative method for nematode management. A total of 25 cover crop species/cultivars, along with three controls were evaluated in greenhouse experiments for their host suitability to the root-lesion nematode Pratylenchus penetrans. Trials were conducted in a completely randomized design using nematode-infested soil and terminated 3 months after planting. Nematodes were extracted from the roots and soil of each crop to determine their final population densities, reproductive factor (Rf = final population density/initial population density), and distributions in the soil and root habitats. Reproductive factor was used to categorize the host suitability of crops. Faba bean cv. Petite produced the greatest nematode population density in all trials, whereas only alfalfa cv. Bullseye constantly demonstrated the poor host ability to P. penetrans. Annual ryegrass, winter rye cv. ND Dylan, and white proso millet also showed poor hosts in most trials. Five cover crops consistently maintained the population throughout the experiments, with Rf values less than 2, and the remaining tested cover crops were suitable hosts for P. penetrans. The majority of the tested cover crops had less than or equal to 30% of the final population residing in the roots after three months of growth in all the trials. This research helps us gain the knowledge on cover crops and P. penetrans interaction and will be useful for potato growers to select better cover crops and avoid susceptible hosts to manage P. penetrans in infested fields to minimize potato yield losses